A gelation mechanism for gelatin/polysaccharide aqueous mixtures. (June 2018) - Wang, Chang-Sheng; Virgilio, Nick; Wood-Adams, Paula M.; Heuzey, Marie-Claude
Abstract: Gelatin/xanthan gum (XG, an anionic polysaccharide) and gelatin/chitosan (CHI, a cationic polysaccharide) aqueous mixtures exhibit enhanced gelation properties compared to the neat components solutions. The gelation properties are governed by the extent of complexation, and therefore are affected by pH and protein to polysaccharide ratio. Inhibition or low extent of complexation results in a slow increase of the elastic modulus ( G′ ), whereas too strong complexation leads to phase separation by precipitation. A maximum G′ is obtained near a pH where phase separation occurs, and the microstructure at this optimal pH is a network structure characterized by biopolymer-rich and biopolymer-poor domains. Based on this rheology-microstructure relationship, a general gelation mechanism on a molecular level for gelatin/polysaccharide aqueous mixtures is proposed. This mechanism is further supported by the results of micro-differential scanning calorimetry. Graphical abstract: Image 1 Highlights: A general mechanism is proposed for the gelation process of gelatin and polysaccharide aqueous mixtures. Mixed gels display enhanced viscoelastic properties as compared to pure polysaccharide and protein solutions. The proposed molecular gelling mechanism is supported by an array of experimental techniques, including rheometry.